Chemoprofiling and antimicrobial activity of medicinal herbs used in the treatment of inflammatory bowel disease: Antimicrobial activity of herbs used in IBD - Alshahrani, Ali; Ali, Abuzer; Abdelwahab, Sayed F. (Cellular and Molecular Biology, 2023)
Inflammatory bowel disease (IBD) is a term utilized to illustrate two different chronic disorders of the gastro-intestinal tract i.e., Crohn’s disease and ulcerative colitis. The symptoms of IBD are mainly characterized by inflammation, including abdominal pain, chronic diarrhoea, weight loss, shortening of the colon and rectal bleeding. The objective of this study was to evaluate the antimicrobial activity and Gas Chromatography-Mass Spectrometry (GC-MS) analysis of herbs used in the treatment of IBD in Saudi Arabia. Ethanolic extracts of five different herbs from Saudi Arabia namely Pimpinella anisum (Anise), Foeniculum vulgare (Fennel), Matricaria chamomilla (Chamomile), Linum usitatissimum (Linseed), and Punica granatum (Pomegranate) were prepared by Soxhlet extraction. The systemic chemical composition of the extracts was identified by GC-MS with their relative concentrations. The ethanolic extract of P. anisum, F. vulgare, M. chamomilla, L. usitatissimum, and P. granatum showed the presence of 35, 42, 34, 37, and 47 chemical components in these extracts, respectively. The five extracts and an equal mixture of them were examined for their antimicrobial activity by broth dilution method against different organisms. These included Gram-positive (Staphylococcus aureus), Gram-negative (Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis and Pseudomonas aeruginosa) bacteria and one yeast (Candida albicans). P. anisum, F. vulgare, M. chamomilla, L. usitatissimum, P. granatum and the mixture of all five extracts had good activity against E. coli (MIC=3.125, 0.050, 6.25, 0.050 and 0.100 mg/ml, respectively). P. granatum also had a MIC of 3.125 mg/ml against S. aureus. In conclusion. the plants’ extracts and an equal mixture of them showed a narrow spectrum of antimicrobial activity against S. aureus, K. pneumoniae, P. mirabilis, P. aeruginosa and C. albicans.